In vitro Effects of Four Native Brazilian Medicinal Plants in CYP3A4 mRNA Gene Expression, Glutathione Levels, and P-Glycoprotein Activity - Mazzari, Andre L. D. A.; Milton, Flora; Frangos, Samantha; Carvalho, Ana C. B.; Silveira, Dâmaris; de Assis Rocha Neves, Francisco; Prieto, Jose M. (Frontiers in Pharmacology, 2016)
Erythrina mulungu Benth. (Fabaceae), Cordia verbenacea A. DC. (Boraginaceae), Solanum paniculatum L. (Solanaceae) and Lippia sidoides Cham. (Verbenaceae) are medicinal plants species native to Brazil shortlisted by the Brazilian National Health System for future clinical use. However, nothing is known about their effects in metabolic and transporter proteins, which could potentially lead to herb-drug interactions (HDI). In this work we assess non-toxic concentrations (100μg/mL) of their infusions for their in vitro ability to modulate CYP3A4 mRNA gene expression and intracellular glutathione levels in HepG2 cells, as well as P-glycoprotein (P-gp) activity in vincristine-resistant Caco-2 cells (Caco-2 VCR). Their mechanisms of action were further studied by measuring the activation of human pregnane X receptor (hPXR) in transiently co-transfected HeLa cells and the inhibition of γ-glutamyl transferase (GGT) in HepG2 cells. Our results show that P-gp activity was not affected in any case and that only Solanum paniculatum was able to significantly change CYP3A4 mRNA gene expression (two-fold decrease, p<0.05), this being correlated with an antagonist effect upon hPXR (EC50 = 0.38mg/mL). Total intracellular glutathione levels were significantly depleted by exposure to Solanum paniculatum (-44%, p<0.001), Lippia sidoides (-12%, p<0.05) and Cordia verbenacea (-47%, p<0.001). The later plant extract was able to decrease GGT activity (-48%, p<0.01). In conclusion, this preclinical study shows that the administration of some of these herbal medicines may be able to cause disturbances to metabolic mechanisms in vitro. Although Erythrina mulungu appears safe in our tests, active pharmacovigilance is recommended for the other three species, especially in the case of Solanum paniculatum.